2017
DOI: 10.1080/10937404.2016.1263586
|View full text |Cite
|
Sign up to set email alerts
|

Geological occurrence, mineralogical characterization, and risk assessment of potentially carcinogenic erionite in Italy

Abstract: Erionite is a zeolite representing a well-known health hazard. In fact, exposure of humans to its fibers has been unequivocally associated with occurrence of malignant mesothelioma. For this reason, a multi-methodological approach, based upon field investigation, morphological characterization, scanning electron microscopy (SEM)/energy-dispersive spectroscopy (EDS) chemical analysis, and structure refinement through X-ray powder diffraction (XRPD), was applied to different samples of potentially carcinogenic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 90 publications
1
29
0
2
Order By: Relevance
“…The framework of pristine sample is characterized by <T1-O> and <T2-O> bond distances of 1.6279 Å and 1.6465 Å respectively (Supplementary Material, Table S3) that are only marginally different in the case of the Fe(II) loaded sample possibly owing to protonation [49]. The R = ( ) values, based on the Jones [72] determinative curves, are higher than those arising from the regression equation of Giordani et al [40]. This is possibly due to the extreme sensitivity of those curves from small variations of average T1-O and T2-O distances that may be attributed to the detrimental effects of an imperfect peak-shape modeling in the case of curled fibers [61].…”
Section: Structural Modificationsmentioning
confidence: 86%
See 1 more Smart Citation
“…The framework of pristine sample is characterized by <T1-O> and <T2-O> bond distances of 1.6279 Å and 1.6465 Å respectively (Supplementary Material, Table S3) that are only marginally different in the case of the Fe(II) loaded sample possibly owing to protonation [49]. The R = ( ) values, based on the Jones [72] determinative curves, are higher than those arising from the regression equation of Giordani et al [40]. This is possibly due to the extreme sensitivity of those curves from small variations of average T1-O and T2-O distances that may be attributed to the detrimental effects of an imperfect peak-shape modeling in the case of curled fibers [61].…”
Section: Structural Modificationsmentioning
confidence: 86%
“…In Italy, the occurrence of erionite was reported in some areas of Sardinia and Veneto regions [37][38][39]. Recently, Giordani et al [26,40] provided a field description and a detailed mineralogical characterization of selected samples of potentially carcinogenic fibrous erionite discovered in the Lessini Mountains (Veneto region, NE Italy).…”
Section: Introductionmentioning
confidence: 99%
“…18 More recently, erionite has also been identified in North Eastern Italy. 19 Baris and colleagues 20 and Artvinli and Baris 21 first reported an outbreak of mesothelioma in 2 small villages in the Anatolian region of Turkey. Some of the villagers also had chronic fibrosing pleurisy.…”
Section: Mineral Fibers Other Than Asbestos Erionitementioning
confidence: 99%
“…The exposure of erionite fibres to humans has been unambiguously linked to malignant mesothelioma, and in vivo studies have demonstrated that, at present, erionite is the most carcinogenic mineral [7]. Accordingly, a growing concern has developed regarding the potential health risks associated with environmental and occupational exposures to erionite in different countries, such as Turkey, the USA, Mexico, Iran and Italy [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A potential carcinogenic hazard of offretite fibres has neither been confirmed nor dismissed so far and it remains unclear whether the mineralogical distinction between erionite and offretite has any health implications. Recently, the epidemiological, mineralogical and toxicological effects of erionite have been intensively investigated [12,[16][17][18][19][20][21][22][23][24][25]. Studies regarding erionite fibres were conducted on their interacting capability and the interactions with micelles and model membranes [26,27].…”
Section: Introductionmentioning
confidence: 99%